2020
DOI: 10.1186/s13071-020-04153-8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the canine vector-borne disease risk in a Mediterranean area

Abstract: Background: The aim of this study was to determine exposure to vector-borne pathogens (VBPs) in populations of dogs living on Greek islands in the Ionian and Aegean seas. Methods: In total, 1154 dogs with different lifestyles and of varying ages and breeds were randomly sampled and examined for the presence of clinical signs compatible with canine vector-borne diseases (CVBDs). Blood was collected from each individual animal. For the detection of antibodies against Leishmania spp., the WITNESS ® Leishmania tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…This result is in accordance with a previous study conducted in Egypt where seropositivity was found to be 23.8% in sheep with the highest infection rate detected in camels 47.8%, followed by 18.0% in goats, 16.0% in cattle and 10.9% in buffalos [26], while in China seroprevalence was up to 63.5% in sheep and goats [43]. The percentage detected here was unexpectantly high compared to the percentages of seropositivity recorded in dogs in Greece [22][23][24], since this is the first report in sheep. Sheep breeding in semiextensive conditions and inadequate deworming program may be responsible for this important difference.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in accordance with a previous study conducted in Egypt where seropositivity was found to be 23.8% in sheep with the highest infection rate detected in camels 47.8%, followed by 18.0% in goats, 16.0% in cattle and 10.9% in buffalos [26], while in China seroprevalence was up to 63.5% in sheep and goats [43]. The percentage detected here was unexpectantly high compared to the percentages of seropositivity recorded in dogs in Greece [22][23][24], since this is the first report in sheep. Sheep breeding in semiextensive conditions and inadequate deworming program may be responsible for this important difference.…”
Section: Discussionsupporting
confidence: 91%
“…The same year in another study, B. burgdorferi antibodies were detected in only 1 out of 1000 dogs, with triple tick-borne pathogen seropositivity [23]. Finally, B. burgdorferi was not detected in a population of 1154 dogs living on Greek Ionian and Aegean islands including Crete in 2020 [24]. However, differences in the seroprevalence among these studies could be attributed to the different areas of dog residency, number of dogs sampled as well as the usage of different method for the detection of antibodies, and therefore different cut off values.…”
Section: Introductionmentioning
confidence: 86%
“…The Mediterranean basin is a suitable environment for the circulation of VBDs in domestic animals; thus, monitoring local canine populations and updated epidemiological data are crucial because available information is often limited to specific countries or to selected pathogens [15,[22][23][24]. Recent studies have demonstrated that several zoonotic VBDs are shared between dog and cat populations throughout the Mediterranean basin, inevitably increasing the chances of spreading among pet populations and transmission to people [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Both stray dogs and free-ranging cats are a major concern in Greece, and are exposed to a plethora of internal parasites and vector-borne pathogens, with some of them having the potential to infect humans ( Section 5.2 ). Greece has been repeatedly reported as an area highly endemic for various canine vector-borne diseases caused by a range of pathogens transmitted to dogs by blood-feeding arthropods, especially ticks, but also fleas, mosquitoes, and sandflies [ 158 ]. Hence, epidemiological vigilance and appropriate control measures are crucial for the prevention and control of these infections, and to minimize the risk of transmission to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Kostopoulou et al reported that out of a total of 1154 randomly sampled dogs of different lifestyles from four Greek islands (Crete and Leros in the Aegean Sea, and Zakynthos and Paxoi in the Ionian Sea), 7.5% were found seropositive for Ehrlichia canis , with an obvious tendency of a higher prevalence to the east and no cases on the Ionian Sea islands [ 158 ]. In total, 2.3% of the dogs were positive for Anaplasma spp., with the highest prevalence on Crete.…”
Section: Tick-transmitted Protozoamentioning
confidence: 99%